2010
DOI: 10.1111/j.1540-8183.2010.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Mechanical Assistance for the Failing Heart

Abstract: (J Interven Cardiol 2010;23:195-202)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…1 Three randomized trials [10][11][12] and their metaanalysis 13 compared the Impella or TandemHeart support with intra-aortic balloon pump in the treatment of cardiogenic shock, showing increased cardiac index at the cost of higher incidence of bleeding; there was no difference in mortality. There are, however, clinical conditions in which intra-aortic balloon pump is clearly insufficient for life support, such as recurrent nontolerated VT, electrical storm, serious mechanical complications of acute myocardial infarction, or cardiac arrest, that does not respond to conventional resuscitation approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Three randomized trials [10][11][12] and their metaanalysis 13 compared the Impella or TandemHeart support with intra-aortic balloon pump in the treatment of cardiogenic shock, showing increased cardiac index at the cost of higher incidence of bleeding; there was no difference in mortality. There are, however, clinical conditions in which intra-aortic balloon pump is clearly insufficient for life support, such as recurrent nontolerated VT, electrical storm, serious mechanical complications of acute myocardial infarction, or cardiac arrest, that does not respond to conventional resuscitation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Their higher hemodynamic effectiveness is, however, counterbalanced by the increased size of catheters and cannulas, which are associated with a higher risk of device-related complications. a life-saving procedure during cardiopulmonary resuscitation or for hemodynamic support in high-risk coronary or electrophysiological interventions, [1][2][3][4][5] particularly in patients with severe left ventricle dysfunction undergoing electrophysiological mapping and tachycardia ablation. [6][7][8][9] To date, only small randomized trials comparing the safety and efficacy of these systems with intra-aortic balloon pump have been published [10][11][12] ; neither clinical nor experimental data on the direct comparison of these circulatory support systems are available.…”
mentioning
confidence: 99%
“…19 They have been shown to be of potential benefit in select patients undergoing high-risk percutaneous coronary intervention, acute myocardial infarction, acute decompensated heart failure, and cardiogenic shock. [20][21][22][23] Because robust clinical evidence is lacking, the Society for Cardiovascular Angiography and Interventions/American College of Cardiology/Heart Failure Society of America/and Society of Thoracic Surgeons have provided a recent expert consensus statement in terms of patient populations that may derive benefit from these devices. 19 In a small single-center study of patients undergoing ablation for scar-related VT, we previously reported that pLVADs provided sufficient hemodynamic support to allow patients to be maintained in VT 2.5-fold longer, with fewer premature terminations required for hemodynamic instability, and allowed more patients to have termination of VT during ablation without any deleterious effects on end-organ perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, the IABP has emerged as the single most effective and widely used circulatory assist device for temporary mechanical assistance of the failing myocardium [4]. Presystolic deflation of the balloon reduces afterload and augments diastolic blood pressure and coronary perfusion.…”
Section: Treatmentmentioning
confidence: 99%
“…The incidence of CS in the Global Utilization of Streptokinase and Tissue Plasminogen Activator (TPA) for Occluded Coronary Arteries (GUSTO-I) trial was 7.2%, and CS was associated with an overall in-hospital mortality of 56% and a 1-year mortality of 80% [2], making AMI complicated by CS the leading cause of in-hospital death for patients admitted with acute coronary syndromes [3]. The most important contributor to the high mortality rate associated with CS is irreversible pump failure that impairs systemic circulation and vital-organ perfusion [4].…”
Section: Introductionmentioning
confidence: 98%